Degradation of highly concentrated organic compounds over a supported Ru–Cu bimetallic catalyst. (29th March 2017) - Lu, Fagui; Yu, Chaoying; Meng, Xu; Chen, Gexin; Zhao, Peiqing
Abstract : A Ru–Cu/Al–Ti-1 catalyst exhibited efficient performance in the CWAO of organic compounds due to synergistic effects between Ru and Cu. Abstract : Ru catalysts and Ru–Cu bimetallic catalysts were prepared via an impregnation method and investigated for the catalytic degradation of high-concentration organics. A series of Al2 O3 –TiO2 -1, Al2 O3 –TiO2 -2, and Al2 O3 and TiO2 -supported Ru and Ru–Cu catalysts were fabricated and characterized by BET, XRD, XPS, H2 -TPR, and TEM to analyze the physicochemical properties of the catalysts. There was a strong interaction between Ru and Cu over Ru–Cu catalysts; moreover, the coexistence of Ru and Cu improved the dispersion of Ru. The addition of Cu increased the performance of Ru catalysts because of the synergistic effects of Ru and Cu for Ru–Cu catalysts; however, the support was also crucial for the catalytic activity. Among the as-prepared Ru and Ru–Cu catalysts, the Ru–Cu/Al2 O3 –TiO2 -1 catalyst, with an Al2 O3 /TiO2 ratio of 1 : 1, exhibited the highest activity, with 91.5% chemical oxygen demand removal after a 2 h reaction at 200 °C and 1.6 MPa oxygen pressure. Furthermore, the pseudo-first-order reaction kinetic model conformed well to the experimental data, with the coefficient correlation greater than 0.98. This catalyst could be reused five times without significant loss of activity.